OPTIMIZING THE DIAGNOSIS OF ALLERGIC REACTIONS TO LOCAL ANESTHETICS IN DENTAL OUTPATIENT CLINICS THROUGH AN IMPROVED EVIDENCE-BASED CLINICAL PROTOCOL - Rаsulоv Shоkhjаkhоn Kаmbаrоvich; Khаbibоvа Nаzirа Nаsullаevnа (Modern American Journals, 2025)
The accurate diagnosis of allergic reactions to local anesthetics remains one of the most challenging aspects of dental outpatient practice. Although true IgE-mediated allergy is exceedingly rare, a substantial number of patients report adverse reactions that closely resemble allergic responses but originate from psychogenic, toxic, or pharmacological mechanisms. Misdiagnosis leads to unnecessary avoidance of effective anesthetics, increased procedural risks, and compromised patient care. This article proposes an optimized, evidence-based clinical protocol designed to improve the diagnostic accuracy of allergic and pseudoallergic reactions in dental settings. The protocol integrates structured history-taking, risk stratification, clinical decision algorithms, and standardized diagnostic tools, while emphasizing the importance of distinguishing immunological reactions from non-immunological events. Two analytical tables summarizing key diagnostic indicators and risk categories are included. The improved diagnostic framework enhances patient safety, supports rational anesthetic selection, and reduces the frequency of misinterpretation of normal physiological responses as “allergy.”
Keywords: Local anesthetics, allergy diagnosis, pseudoallergy, clinical protocol, dental practice, hypersensitivity, risk stratification, diagnostic algorithm.